Assessment of the Evaluation Framework for Energy Maximising Control Systems for the Wavestar Wave Energy Converter - Windt, Christian; Faedo, Nicolas; Penalba, Markel; Ringwood, John V. (Proceedings of the American Control Conference, 2019)
During the design process and evaluation of energy maximising control systems (EMCSs) for wave energy converters (WECs), control techniques rely heavily on numerical modelling. For fast computation, these numerical models are mostly based on low-fidelity boundary element method (BEM) codes and linear hydrodynamic models. However, to ensure optimal performance in a physical environment, more realistic, high-fidelity numerical frameworks, such as Computational Fluid Dynamics (CFD) based numerical wave tanks (CNWTs), should be considered during the evaluation of EMCSs. This paper investigates the influence of different numerical evaluation frameworks on the performance evaluation of EMCSs. The Wavestar WEC, subject to three different EMCSs with varying aggressiveness, i.e. resistive, reactive and moment-based control, is chosen as the case study. Results show that more aggressive EMCSs require high-fidelity numerical modelling to correctly evaluate their performance.